Alkyd Printing Inks from Waste Frying Oil - PHUNPHOEM, Sivaphol; SARAVARI, Onusa; SUPAPHOL, Pitt (Walailak Journal of Science and Technology (WJST), 2020)
Alkyd-based printing ink vehicles were successfully prepared from waste frying oil. Three alkyd resins were synthesized using different ratios of phthalic anhydride. Properties of the 3 prepared resins were measured and compared with virgin oil alkyd resin and commercial alkyd resin. Viscosities of the obtained ink vehicles ranged from 8.6 to 34.9 poises. The vehicles were also completely compatible with carbon black for formulating black printing inks. Preliminary properties of the 3 formulated inks were evaluated and compared with black printing ink prepared from virgin oil alkyd and commercial alkyd. The formulated inks had satisfactory viscosity and tackiness as properties suitable for a variety of printing applications. The 3 synthesized inks had rub resistance values ranging from 4.61 to 5.75 %, slightly higher than the rub resistance of virgin oil alkyd ink and commercial alkyd ink. Particle fineness and water tolerance properties of the 3 formulated inks were comparable with virgin oil alkyd ink and commercial alkyd ink. Results suggested that waste frying oil has potential application as a raw material in the printing ink industry.